Persistent gamma oscillations in superficial layers of rat auditory neocortex: experiment and model - Traub, Roger D (Blackwell Science Inc, 2005)
Persistent in vitro gamma oscillations, induced by bath application of carbachol and kainate (amongst other drugs), were discovered by Eberhard Buhl and collaborators in 1998. The oscillations are robust, in that they can continue for hours; but the oscillations are also intricate in their mechanisms: they depend upon phasic synaptic excitation and inhibition, upon electrical coupling between interneurones and between pyramidal neurones, and – at least in neocortex – they depend upon complex intrinsic properties of some of the neurones.